Perlindungan Hukum Terhadap Franchisee Akibat Pemutusan Sepihak dalam Perjanjian Franchise - I Gusti Ngurah Md Rama Andika; Ni Luh Made Mahendrawati; Ida Ayu Putu Widiati (Warmadewa Press, 2021)
In the implementation of a franchise agreement, it is not uncommon for the agreement not to be implemented due to a unilateral termination by the franchisor. Considering that the franchisee in the franchise agreement is in a weaker position, in the event of a unilateral termination, it will suffer a large loss. However, in the laws and regulations, there are no clear arrangements for the protection of franchisees who experience unilateral termination who actually experience losses. The purpose of this study is to analyze the franchise agreement may be terminated unilaterally by the franchisor and the legal protection of the franchisee against the unilateral termination of the franchise agreement by the franchisor. This study uses normative legal research methods using primary legal materials, with the types of approaches used are statutory approaches, case approaches and conceptual approaches. Legal sources are then analyzed systematically. Based on the results of the study, it can be concluded that basically the franchise agreement cannot be terminated unilaterally unless the void conditions stated in the contract have been fulfilled and legal protection for the franchisee against the losses he has suffered can be sued for compensation based on default.